Enhanced Surveillance of Acute Hepatitis B and C in Four Health Regions in Canada, 1998 TO 1999 - Shimian Zou; Jun Zhang; Martin Tepper; Antonio Giulivi; Beverley Baptiste; Gerry Predy; Darlene Poliquin; Manon Morin; Donna Jones; Joy Loewen; Margaret Ogonowski; Stephen Moses; et al. (Canadian Journal of Infectious Diseases)
OBJECTIVE: To assess the incidence and risk factors for acute hepatitis B and acute hepatitis C in a defined Canadian population.